Combination of a geolocation database access with infrastructure sensing in TV bands - Dionísio, Rogério (2016)
Submitted by Lurdes Grilo (lurdesgrilo@ipcb.pt) on 2016-01-04T12:42:03Z No. of bitstreams: 1 1687-1499-2014-210.pdf: 1662924 bytes, checksum: 03e099d7fdc7f861799916372ab637d4 (MD5)